Find values of y such that: log2(11y–3)–log2(3) –2log2(y) = 1

NB.: Treat all log as log2 for purpose of formatting log(x) - log(z) = log(x/z) alog(b) = log(b^a) log((11y - 3)/3) - log(y^2) = 1 log((11y - 3)/3y^2) = 1 11y - 3 / 3y^2 = 2^1 11y - 3 = 6y^2 6y^2 - 11y + 3 = 0 (3y - 1) (2y - 3) = 0 y = 1/3 or 1.5

Answered by Shrinivas A. Maths tutor

4655 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

integrate xsin(x)


A curve has parametric equations x = 2 sin θ, y = cos 2θ. Find y in terms of x


find the derivative of the following equation: a) y = 5x^3 - 4x^-4 + xb


How do you find the point of intersection of two vector lines?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences